2021
DOI: 10.3390/ijms22063185
|View full text |Cite
|
Sign up to set email alerts
|

T and B Lymphocyte Transcriptional States Differentiate between Sensitized and Unsensitized Individuals in Alpha-Gal Syndrome

Abstract: The mechanisms of pathogenesis driving alpha-gal syndrome (AGS) are not fully understood. Differences in immune gene expression between AGS individuals and non-allergic controls may illuminate molecular pathways and targets critical for AGS development. We performed immune expression profiling with RNA from the peripheral blood mononuclear cells (PBMCs) of seven controls, 15 AGS participants, and two participants sensitized but not allergic to alpha-gal using the NanoString nCounter PanCancer immune profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 65 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…In addition, we recently showed that the transcriptional immune profiles in circulating PBMCs from alpha-galsensitized human subjects were distinct from controls without detectable alpha-galsIgE. There was increased expression of genes associated with Ag presentation, MHC-II surface expression, and cytokines and chemokines associated with itch and allergic dermatitis, including IL-13RA, which encodes the receptor for the Th2 cytokine IL-13 (19). These findings suggest that the generation of alpha-galsIgE may depend in part on MHC-IImediated Ag presentation to CD4 1 Th2 cells, although to date, this has not been formally demonstrated.…”
Section: Sensitization Phase In Agsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we recently showed that the transcriptional immune profiles in circulating PBMCs from alpha-galsensitized human subjects were distinct from controls without detectable alpha-galsIgE. There was increased expression of genes associated with Ag presentation, MHC-II surface expression, and cytokines and chemokines associated with itch and allergic dermatitis, including IL-13RA, which encodes the receptor for the Th2 cytokine IL-13 (19). These findings suggest that the generation of alpha-galsIgE may depend in part on MHC-IImediated Ag presentation to CD4 1 Th2 cells, although to date, this has not been formally demonstrated.…”
Section: Sensitization Phase In Agsmentioning
confidence: 99%
“…In $20% of AGS cases, the clinical phenotype involves only gastrointestinal symptoms, primarily severe persistent abdominal cramping, diarrhea, and gastroesophageal reflux (20). Like conventional food allergies, AGS can develop during childhood (20,21) but also arises in older adults who have tolerated mammalian meat for decades (19,22).…”
mentioning
confidence: 99%
“…Alpha-gal syndrome (AGS) is an immune-mediated disorder caused by hypersensitivity responses to glycan galactose-alpha-1,3-galactose (alpha-gal). A significant difference between usual food allergies and AGS is the reaction time, with symptom onset occurring two or more hours after alpha-gal consumption [31].…”
Section: Physiopathologymentioning
confidence: 99%
“…It works by binding to the Fc region of IgE antibodies, blocking the binding to specific receptors on mast cells and basophils [59,60,68], preventing their degranulation and therefore the appearance of allergic manifestations. Omalizumab should be initiated before the OIT and continued for a few more weeks in parallel [31,69,70]. The recommendation considers both the increase of the safety profile of immunotherapy and its effectiveness.…”
Section: Omalizumabmentioning
confidence: 99%
“…Mattison et al [15] performed a microbiological, physicochemical, and immunological analysis of a commercial cashew nut-based yogurt, which indicated that it was not suitable for individuals with a cashew nut allergy. Iweala and coworkers [16] investigated, in turn, a unique type of allergy. They demonstrated that in alpha-gal syndrome, peripheral blood T and B lymphocyte transcriptional states could differentiate between sensitized and sensitized individuals.…”
mentioning
confidence: 99%